Teresa of Avila: The will and the weaving - Madden, Kathryn (Journal of religion and health, 1994)
For more than forty-five years as a Carmelite nun in the sixteenth century, Teresa of Avila suffered from great physical pain. We see in her life how disciplined prayer can become a healing experience that moves from minimal psychic representation to full symbolic representation. After a brief examination of Teresa's life, two theoretical perspectives on somatic manifestation will be reviewed: the theory of conversion hysteria of the classical Freudian school, and the differentiation Joyce McDougall draws between hysterical and psychosomatic phenomena. For the psychosomatic, as the mystic, the void of wordless space has significance. Following after McDougall on the suffering body, a third perspective will be offered: the concept of conscious body suffering as a means to inner change.